2017
DOI: 10.4067/s0718-95162017005000006
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen availability and early corn growth on plowed and no-till soils amended with different types of cover crops

Abstract: Heavy application of nitrogen (N) fertilizers to agroecosystems contributes to water pollution and emission of nitrous oxide (N 2 O), an atmospheric constituent implicated in the greenhouse effect and stratospheric ozone depletion. The incorporation of cover crops biomass into agricultural soil is a practice that could provide a portion of the N needed by growing crops, and thereby could help reduce N fertilizer input and N loss from agroecosystems. Although the cover crop composition and the tillage managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…In particular, research has shown that some cover crops can provide at least part of the mineral N needed for optimum crop yield, leading to possible reductions in the amount of synthetic N fertilizer applied to agricultural fields. In addition, slow-degrading cover crop plant materials such as rye (Secale cereale L.) release mineral N in synchrony with N demand of growing crops and thus enhance N uptake 32 . These results argue for the supplementation of NT farming with other strategies to enhance N use efficiency and reduce diffuse N pollution.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, research has shown that some cover crops can provide at least part of the mineral N needed for optimum crop yield, leading to possible reductions in the amount of synthetic N fertilizer applied to agricultural fields. In addition, slow-degrading cover crop plant materials such as rye (Secale cereale L.) release mineral N in synchrony with N demand of growing crops and thus enhance N uptake 32 . These results argue for the supplementation of NT farming with other strategies to enhance N use efficiency and reduce diffuse N pollution.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the decrease was significantly different from the increase in the proportion of sago pulp waste in the mixtures. Maize growth experiences a vegetative growth phase from week 4 until the plant enters the final vegetative stage at 8 weeks after planting, where the plant's need for nitrogen is very high (Ladan and Jacinthe, 2017). Nitrogen is an essential constituent of amino acids, amides, nucleotides and nucleoproteins, and is essential for cell division, cell enlargement and growth.…”
Section: Maize Growth (Experiments 2)mentioning
confidence: 99%
“…Due to its high yield, fodder advantages and adaptability to cultivation, this crop is grown in different regions of the country. The most important factor that determines the yield of agricultural crops is mineral nutrition [1][2][3]. When cultivating maize, it is important to apply the necessary treatment to the plants in the required amount and the optimal ratio of basic nutrients and microelements.…”
Section: Introductionmentioning
confidence: 99%